Ne davimo Beograd (Serbia) as the example of the the new wave urban movement - Korzeniewska-Wiszniewska, Mirella (Balcanica Posnaniensia. Acta et studia, 2023)
The Serbian socio-political initiative Ne da(vi)mo Beograd (We will not give/flood Belgrade) is defined as a local political movement initiated by the citizens of Belgrade. This movement is one of the new urban social movements emerging from the so-called new social movements of the second generation and indicate the dynamic development of grassroots civic initiatives that want to change the local reality in the face of lack of trust in politicians from the central government, as people not interested in changing the situation of the average citizen. Urban movements, in turn, are characterized by initiatives aimed at improving the lives of the inhabitants of a given town. The article aims to analyze the activities of this movement as an element of a wider activity, known in Serbia as the Civic Front, which brings together local political organizations that are active in individual towns. It also aims to try to answer the question where the border of a social movement ends and the activity of a political organization begins. Ne da(vi)mo Beograd seems to be an initiative that goes beyond unambiguous definitions and may be an example of new, new civic activities that need a new definition, while setting a new framework for activity.